Relationship of Food Services and Patients Satisfaction in Medan Advent's Public Hospital - Nurul Hidayah; Asyiah Simanjorang; Asriwati Asriwati; Lucia Lastiur (Newinera Publisher, 2021)
Food service in hospital nutrition installations is a form of service activity for patients who are hospitalized which aims to meet the nutritional needs of patients. This study aimed to analyze the relationship between food services and satisfaction of inpatients at the Adventist General Hospital. Field. This study used a survey research method with a cross sectional approach. The data collection technique used a questionnaire. Population of 156 people with a sample of 112 people based on Slovin calculations. Based on the results of the chi-square statistical test, it was found that the variables of mealtime (p = 0,000), food appearance (p = 0,000), food taste (p = 0,000), waiter friendliness (p = 0,000), cleanliness of tools and food (p. = 0.012), and food variation (p = 0.00). The result of multiple logistic regression test shows that the meal time variable has a significant effect on patient satisfaction. There is a relationship, meal time, food appearance, taste of food, waiter friendliness, cleanliness of equipment and food, variety of food with patient satisfaction with food service at the Medan Adventist General Hospital. It is recommended to the special hospital nutrition installation that in food processing always pay attention to the main factors in food processing so that the level of patient satisfaction continues to increase and still maintains the quality and quality of food service.